Escherichia coli BMP-2 showed comparable osteoinductivity with Chinese hamster ovary derived BMP-2 with demineralized bone matrix as carrier. (4th March 2019) - Jin, Yuan-Zhe; Zheng, Guang-Bin; Lee, Jae Hyup
Abstract: Escherichia coli bone morphogenetic protein-2 (ErhBMP-2) had a larger yield but less osteoinductivity than Chinese hamster ovary cell bone morphogenetic protein-2 (CrhBMP-2). Since the release profile of rhBMP-2 affects its osteoinductivity, an appropriate carrier could improve the effect of ErhBMP-2. Demineralized bone matrix (DBM) was one of the most widely used bone substitutes, but few studies evaluated the osteoinductivity of ErhBMP-2 while it was carried by DBM. Therefore, we compared the osteoinductivity of ErhBMP-2 with CrhBMP-2 with DBM as the carrier of each. In vitro results showed ErhBMP-2 had slightly less osteoinductivity than CrhBMP-2. However, with DBM as the carrier, ErhBMP-2 induced significantly more bone regeneration in rat calvaria defects. Therefore, ErhBMP-2 might have comparable osteoinductivity with CrhBMP-2 while carried by DBM.